Chronic Thromboembolic Pulmonary Hypertension: the therapeutic assessment - Simeone, Beatrice; Maggio, Enrico; Schirone, Leonardo; Rocco, Erica; Sarto, Gianmarco; Spadafora, Luigi; Bernardi, Marco; D’Ambrosio, Luca; Forte, Maurizio; Vecchio, Daniele; Valenti, Valentina; Sciarretta, Sebastiano; et al. (Frontiers in Cardiovascular Medicine, 2024)
Chronic Thromboembolic Pulmonary Hypertension (CTEPH) is a severe and complex condition that evolves from unresolved pulmonary embolism, leading to fibrotic obstruction of pulmonary arteries, pulmonary hypertension, and potential right heart failure. The cornerstone of CTEPH management lies in a multifaceted therapeutic approach tailored to individual patient profiles, reflecting the disease's heterogeneity. This review delves into the current therapeutic strategies for CTEPH, including surgical pulmonary endarterectomy (PEA), balloon pulmonary angioplasty (BPA), and targeted pharmacological treatments such as PDE5 inhibitors, endothelin receptor antagonists, sGC stimulators, and prostanoids. Lifelong anticoagulation is also highlighted as a preventive strategy against recurrent thromboembolism. Special emphasis is placed on the interdisciplinary nature of CTEPH care, necessitating collaboration among PEA surgeons, BPA interventionists, PH specialists, and thoracic radiologists to ensure comprehensive treatment planning and execution. The review underscores the importance of selecting an appropriate treatment modality based on the patient's specific disease characteristics and the evolving landscape of CTEPH treatment, aiming to improve patient outcomes through integrated care strategies.